Analysis of helicobacter pylori antimicrobial susceptibility and virulence genes. - Goh, Hui Lin. (2009)
Helicobacter pylori, which causes gastric ulcers and cancers, contains the polymorphic virulence genes cagA and vacA. Differences in the cagA EPIYA motifs and polymorphisms of vacA signal (s), middle (m) and intermediate (i) regions were thought to be important in determining disease severity. This study aims to determine cagA and vacA polymorphisms of H. pylori isolated from Singapore’s multi-ethnic population. Furthermore, a 12-year trend of antibiotic resistance from the isolates was studied. A total of 86 H. pylori isolates were obtained from patients with dyspeptic symptoms. Antibiotic resistance was determined by Etest; DNA was extracted from the isolates and allelic variation of virulence genes were determined by PCR and sequencing. High metronidazole resistance and increasing clarithromycin and levofloxacin resistance were observed through the 12 years. Chinese patients predominantly carried vacA s1/m2/i1 strains as compared to non-Chinese who mainly carried s1/m1/i1 (p<0.001). Furthermore, the Chinese isolates mainly possessed CagA with EPIYA-ABD motif, whereas non-Chinese isolates predominantly carried the EPIYA-ABC motif (p<0.001). With increased antibiotic resistance, enforcement of alternative treatments is essential. Marked polymorphic differences of cagA and vacA genotypes were observed between ethnic groups. Though vacA was not correlated with disease, cagA EPIYA genotypic differences may identify high-risk patients.